Labour market accessing of two Pedagogy groups from the University of Malaga - Matas-Terrón, Antonio (My University, 2019)
Abstract An exploratory analysis of the labour insertion of Pedagogy students from the University of Malaga belonging to the groups of 2009-10 and 2013-14 is presented. Data from 180 students, provided by the Quality Unit of the University of Malaga, were used. As an indicator of labor insertion, social security affiliation has been used. An Exploratory Single-Case Evaluation design was carried out. A graphic comparison of the trend in both groups has also been developed. Findings show a progressive soft tendency to access. Resumen Se presenta un análisis exploratorio de la inserción laboral de estudiantes de Pedagogía de la Universidad de Málaga pertenecientes a los grupos de 2009-10 y 2013-14. Se utilizaron datos de 180 estudiantes, proporcionados por la Unidad de Calidad de la Universidad de Málaga. Como indicador de inserción laboral, se ha utilizado la afiliación a la seguridad social. Se llevó a cabo un diseño exploratorio de evaluación de un solo caso. También se ha desarrollado una comparación gráfica de la tendencia en ambas cohortes. Los resultados muestran una tendencia suave progresiva para acceder.
Inserción laboral del alumnado de Pedagogía de la Universidad de Málaga: estudio de dos grupos de graduados
Matas-Terron, A. (n.d.). Labour market accessing of two Pedagogy groups from the University of Malaga. Retrieved from osf.io/preprints/socarxiv/mk7uy
Keywords: Pedagogos - Oferta y demanda - Universidad de Málaga; Pedagogía - Málaga; Mercado de trabajo; España; Evaluation; Exploratory Single Case Evaluation Method; Labour Market; Program Evaluation; University